2002
DOI: 10.1063/1.1431275
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the I2(X)⋯Ar isomers population in a free-jet expansion: Thermodynamics versus kinetic control

Abstract: The one-atom cage effect in I 2 (B)-Ar : Evidence that caging is inefficient for the T-shaped isomer Erratum: "On nonadiabatic molecular dynamics simulations of the photofragmentation and geminate recombination dynamics in size-selected I 2 − Ar n cluster ions" [J.Nonadiabatic molecular dynamics simulations of the photofragmentation and geminate recombination dynamics in size-selected I 2 − Ar n cluster ions A molecular dynamics simulation addressing the problem of thermodynamic versus kinetic control of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 11 publications
0
47
0
1
Order By: Relevance
“…The overall agreement between already published theoretical predictions 18,35 with our experimental results of the ground and excited state intermolecular vibrational energy levels indicate that calculations can qualitatively and perhaps quantitatively complement experimental efforts aimed at interrogating these phenomena. Systematic studies are currently ongoing in our laboratory that are aimed at characterizing the thermodynamic cooling 36 of the He¯ICl(X) complexes down to the lowest energy intermolecular vibrational levels of the complex, at comparing and contrasting the rotational product state distributions following vibrational predissociation from T-shaped 17,18,30 and linear He¯I 35,37 Cl(B,vЈϭ2,3) orientations, and at further characterizing the ground state interactions using twolaser, pump-probe spectroscopic methods.…”
Section: Discussionmentioning
confidence: 99%
“…The overall agreement between already published theoretical predictions 18,35 with our experimental results of the ground and excited state intermolecular vibrational energy levels indicate that calculations can qualitatively and perhaps quantitatively complement experimental efforts aimed at interrogating these phenomena. Systematic studies are currently ongoing in our laboratory that are aimed at characterizing the thermodynamic cooling 36 of the He¯ICl(X) complexes down to the lowest energy intermolecular vibrational levels of the complex, at comparing and contrasting the rotational product state distributions following vibrational predissociation from T-shaped 17,18,30 and linear He¯I 35,37 Cl(B,vЈϭ2,3) orientations, and at further characterizing the ground state interactions using twolaser, pump-probe spectroscopic methods.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism involves long-range interaction between the molecular complex and the polarizable carrier gas. [58] The formation of a collisional complex with the heavy carrier gas increases the internal energy, which allows the isomerization barriers to be surmounted. [59] …”
Section: Angewandte Chemiementioning
confidence: 99%
“…One or a limited number of conformers are thus populated. However, numerous studies have shown that the formation of complexes in a supersonic expansion is not always under thermodynamic control [39][40][41][42][43] Higher energy conformers can be observed in the supersonic expansion; thermodynamically stable forms might be absent if the barrier to their formation is too high (kinetic control) [44][45][46].…”
Section: A Zehnackermentioning
confidence: 99%
“…This so-called solvent-assisted conformational isomerisation (SACI) involves formation of transient complexes in the collision zone, the binding energy of which is used for overcoming the isomerisation barrier. This process is also feasible with a heavy noble gas [39].…”
mentioning
confidence: 98%